Backmatter (Author Guideline, Publication Ethics, Copyright Transfer Agreement for Publishing Form) (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2012)
Backmatter (Author Guideline, Publication Ethics, Copyright Transfer Agreement for Publishing Form)